Arcyriaflavin a, a cyclin D1-cyclin-dependent kinase4 inhibitor, induces apoptosis and inhibits proliferation of human endometriotic stromal cells: a potential therapeutic agent in endometriosis - Tomoko Hirakawa; Kaei Nasu; Yoko Aoyagi; Kanetoshi Takebayashi; Hisashi Narahara (BMC, 2017)
Abstract Background We previously showed that microRNA-503 (miR-503) transfection into endometriotic cyst stromal cells (ECSCs) induced cell cycle arrest at the G0/G1 phase by suppressing cyclin D1. This finding prompted us to evaluate the potential therapeutic effects of cyclin D1 inhibitors in endometriotic cells. This study aimed to determine whether arcyriaflavin A, a representative inhibitor of cyclin D1-cyclin-dependent kinase 4 (CDK4), is beneficial in the treatment of endometriosis. Methods ECSCs were isolated from the ovarian endometriotic tissues of 32 women. The effects of arcyriaflavin A on cell viability and proliferation, vascular endothelial growth factor A expression, apoptosis, and cell cycle progression were evaluated using a modified methylthiazoletetrazolium assay, enzyme-linked immunosorbent assay (ELISA), Caspase-Glo® 3/7 assay, and flow cytometry. Results Arcyriaflavin A significantly inhibited cell viability, proliferation, and angiogenesis of ECSCs as assessed using the 5-bromo-2-deoxyuridine (BrdU) and methylthiazoletetrazolium bromide (MTT) assays, and vascular endothelial growth factor (VEGF) ELISA. Arcyriaflavin A induced apoptosis as shown in the Caspase-Glo® 3/7 assay and cell death detection ELISA whilethe cell cycle was arrested at the G0/G1 phase. Conclusion The findings indicate that cyclin D1-CDK4 inhibitors may be promising candidates for the treatment of endometriosis. This is the first study to demonstrate the potential usefulness of arcyriaflavin A as a therapeutic agent for endometriosis. Further studies of the effects of cyclin D1-CDK4 inhibitors on endometriosis may provide useful information on pathogenesis and treatment.